2018
DOI: 10.1002/advs.201800177
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Nitrogen and Cobalt Codoped Hollow Carbon for Electrochemical Syngas Production

Abstract: Electrochemical conversion of CO2 and H2O into syngas is an attractive route to utilize green electricity. A competitive system economy demands development of cost‐effective electrocatalyst with dual active sites for CO2 reduction reaction (CO2RR) and hydrogen evolution reaction (HER). Here, a single atom electrocatalyst derived from a metal–organic framework is proposed, in which Co single atoms and N functional groups function as atomic CO2RR and HER active sites, respectively. The synthesis method is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 55 publications
2
45
0
Order By: Relevance
“…[61a] This result was further confirmed by Song et al, who synthesized a Co SACs (3.4 wt%) constructed from Co–C 2 N 2 moieties . The Co SACs reached a nearly 100% FE at potential less than −0.7 V. Interestingly, the CO selectivity of Co SAC dramatically decreased to 9.8% after the addition of potassium thiocyanate, confirming that the active site for CO 2 RR is Co–N 2 …”
Section: Electrochemical Co2 Conversion On Single‐atom Catalystssupporting
confidence: 65%
See 3 more Smart Citations
“…[61a] This result was further confirmed by Song et al, who synthesized a Co SACs (3.4 wt%) constructed from Co–C 2 N 2 moieties . The Co SACs reached a nearly 100% FE at potential less than −0.7 V. Interestingly, the CO selectivity of Co SAC dramatically decreased to 9.8% after the addition of potassium thiocyanate, confirming that the active site for CO 2 RR is Co–N 2 …”
Section: Electrochemical Co2 Conversion On Single‐atom Catalystssupporting
confidence: 65%
“…I) CO FEs of Co–N 2 , Co–N 3 , and Co NPS at different applied potentials. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Electrochemical Co2 Conversion On Single‐atom Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a control experiment where Co–N 2 , Co–N 3, and Co–N 4 catalysts were tested for CO 2 RR, it was observed that Co–N 2 demonstrated the highest FE CO of 95% at −0.68 V compared to 63% at −0.53 V for Co–N 3 and 7% with Co–N 4 catalysts . These results were also verified by a Co single atom on hollow carbon structure (Co‐HNC) catalyst that also consisted of Co–N 2 active sites and demonstrated an unprecedented FE CO of ≈100% . In recent times, Co–N 5 sites anchored on polymer derived N‐doped porous carbon spheres were also reported to be active for CO 2 RR…”
Section: Active Sites In Metal‐carbon Catalystsmentioning
confidence: 78%